Correlation study on different temperature-humidity of highly thermal graphene hybridzation conductive ink - Mohammad Noor, Norida (2023)
This research is about the correlation study on different temperature-humidity of highly thermal graphene hybridization conductive ink. The aim of this research is to develop and formulate a highly thermal graphene hybridization conductive ink combining graphene nanoparticle (GNP), silver flakes (Ag), and silver acetate (SA) as conductive fillers mixed with chemical and organic solvents. Currently, the use of soldering for die-attach can cause thermal stress and has environmental concerns. Conductive ink was considered as an alternative, but it had limitations in dispersibility and conductivity. Environmental factors such as moisture and extreme temperature changes can also affect the conductivity of the ink over time. This new material would have improved properties that overcome the limitations of traditional materials while preserving their beneficial characteristics. To develop a highly thermal graphene hybridization conductive ink, a new formulation of conductive ink is formulated using graphene nanoparticles (GNP), silver flakes (Ag), and silver acetate (SA) as conductive fillers mixed with organic solvents. In order to turn the batch of substances into powder, they are sonicated and followed by stirring to form the mixture into a powder. Before curing at 250°C for 1 hour, the powder are dripped with organic solvents, 1-butanol, and terpineol and mixed using a thinky mixer machine to form a paste. Using a mesh stencil, the GNP hybrid paste was printed on copper substrates. Cyclic testing was conducted using a cyclic bending test machine and a cyclic torsion test machine in a heat chamber with different temperature-humidity based on the numbers of lamps. The new formulation are then characterized based on the electrical and mechanical behaviour. In order to evaluate the performance, the resistivity of the hybrid GNP conductive ink at room temperature is set as the baseline and compare it to the resistivity readings obtained at varying temperatures-humidity levels. After the twisting and bending test, the GNP hybrid formulation reliability was evaluated. GNP hybrid room temperature baseline and GNP hybrid after given different temperature-humidity were compared in terms of electrical and mechanical properties. The average resistivity measurement at all points of sample remains stable or decreases as the temperature increase. It demonstrate that the electrical conductivity of the ink does not degrade significantly as the temperature-humidity increases, indicating that the ink are able to maintain its structural integrity and properties with certain temperature range. This signifies that a hybrid conductive ink has good thermal stability and demonstrates that mixing GNP with silver improves the performance of electrical conductivity. Future research should focus on improving the stability and reliability of stretchable conductive inks under various temperature and humidity conditions.